Cause-specific mortality and heart failure readmissions according to the HFA-PEFF algorithm in patients hospitalised for heart failure with preserved ejection fraction. (25th November 2020) - Verbrugge, F.H; Reddy, Y.N.V; Carter, R.E; Borlaug, B.A
Abstract: Background: The HFA-PEFF algorithm has been recently developed and is recommended by the European Society of Cardiology to make a diagnosis of heart failure with preserved ejection fraction (HFpEF). Based on functional echocardiography criteria, morphological criteria, and natriuretic peptide levels, a score from 1 to 6 is obtained with higher scores indicating a higher probability of HFpEF. Purpose: This study investigates the prognostic value of the HFA-PEFF score in HFpEF patients hospitalised for decompensation. Methods: This retrospective cohort study includes consecutive patients with HFpEF, admitted to Mayo Clinic Rochester between 2010–2015 and requiring treatment with intravenous loop diuretics for congestion. The HFA-PEFF score was calculated for all patients with echocardiography data available within 1 year and natriuretic peptide levels obtained upon admission. The study population was subsequently stratified according to HFA-PEFF score ≤4 (n=79), =5 (n=93), or =6 (n=271). Incidence rates of recurrent heart failure admissions per 100 patient-years of follow-up, time to all-cause mortality, and mortality causes were compared among strata. Results: In 443 patients with HFpEF (78±12 years; 60% women), higher HFA-PEFF score was associated with older age, female gender, higher systolic blood pressure, and worse renal function. Heart failure readmission rates were higher in patients with HFA-PEFF score =5 [46.0 (38.5–53.5)] or HFA-PEFF score =6 [45.0 (40.1–49.8)] versus HFA-PEFF score ≤4 [28.9 (22.7–35.0); P-value<0.001 for differences; see upper panel figure]. Increasing HFA-PEFF score was associated with a shorter median survival (P-value<0.001), which was 65 months (36–89 months) in HFA-PEFF score ≤4, 45 months (26–59 months) in HFA-PEFF score =5, and 28 months (22–42 months) in HFA-PEFF score =6 (see lower panel figure). The proportions of deaths directly related to heart failure were comparable among HFA-PEFF strata (49% versus 49% versus 52%, respectively; P-value=0.903), as was the contribution of cardiovascular death (60% versus 57% versus 63%, respectively; P-value=0.662). Overall, few differences in patterns of mortality causes were observed among strata. There was a lower contribution of primary respiratory disease (mainly chronic obstructive pulmonary disease) to mortality in patients with a higher HFA-PEFF score (26% versus 19% versus 6%, respectively; P-value<0.001). Conclusions: Higher HFA-PEFF score in hospitalized patients with HFpEF is associated with increased risk of subsequent heart failure readmissions and all-cause mortality, which includes both heart failure specific and non-heart failure mortality. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Belgian American Educational Foundation (B.A.E.F.); Special Research Fund (BOF) of Hasselt University (Hasselt, Belgium)